The role of Aloe vera in various fields of medicine and dentistry - Andey Venkata Subhash; S. Suneela; Ch. Anuradha; S. N. Bhavani; M. Srinivas Minor Babu (Wolters Kluwer Medknow Publications, 2014)
Aloe vera is a cactus like plant that actually is part of the lily family. There are more than 300 varieties of the Aloe plant, but the Aloe barbadensis variety exhibits the best medicinal properties. It has strong antiseptic, antibacterial, fungicidal and virucidal properties. It promotes cell growth and is neurologically calming and acts as a detoxifying agent. Others provide nutritional support and some increase the regenerative potential of tissues while others act with anti-inflammatory responses. This article reviews the uses of the plant in different fields of medicine and dentistry.